Post flowering assimilate availability regulates oil fatty acid composition in sunflower grains - Echarte, Maria Mercedes (2012)
Fatty acid composition of Helianthus annuus L. (sunflower) oil depends on intercepted solar radiation per plant (ISR) during grain filling. This effect could be accounted by the assimilate availability for the grains (the source-sink ratio). However, the current physiological-biochemical knowledge does not consider any effect of carbon availability on oil fatty acid composition. The objective of this work was to address the regulation of fatty acid composition by assimilate supply to sunflower grains. A wide range of source-sink ratios was obtained by manipulating either the source or the sink during grain filling. Assimilate supply was also modified by injecting sucrose to the receptacle of sunflower capitula. Grain weight and oil content depended on both ISR and source-sink ratio in a curvilinear manner. When sink size was decreased by grain excision, ISR failed to explain oil fatty acid composition while source-sink ratio appropriately described it. Sucrose injection significantly increased grain weight, oil content and oleic acid percentage of shaded plants. It is concluded that effects of ISR on fatty acid composition are a consequence of changes in assimilate availability for grain oil synthesis. To explain these results a conceptual model is proposed: when assimilate supply limits grain growth and oil synthesis, mainly linoleic acid is synthesized. As the assimilate supply increases, oleic acid desaturation process gets saturated and oleic acid accumulates.